MEDICOLEGAL AND ETHICAL ASPECTS OF A DEATH CASE DUE TO EPILEPSY: CLINICAL CASE, CLINICAL FORENSICS, OR FORENSIC PATHOLOGY? - Adji Suwandono; Hedva Rayna Hitipeuw; Funica Asri Rachmawaty; Sandy Adi Nugraha Pratama; Alfonsus Aryo Sunu Bakti (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: An unwitnessed death in a man with epilepsy, found in a bathroom with a head injury and immersion, raises key clinical and forensic concerns. This case highlights the complex intersection between epilepsy-related death, head trauma, and possible drowning. Case Presentation: A 39-year-old man with a history of epilepsy was found unconscious in the bathtub, face down with his head submerged and a bleeding forehead wound, approximately 10 minutes after showering. The man had a history of monthly generalized tonic-clonic seizures with recurrent falls and head injuries, and was on regular antiepileptic medicine. On admission, he was unresponsive with a GCS of E1V1M1, absent vital signs, dilated pupils, decreased skin temperature, and a laceration wound on the forehead. An ECG showed asystole. Conclusion: This case reviews the high risk of sudden death in patients with epilepsy, likely involving seizure-induced trauma and possible drowning. It emphasizes the need for comprehensive epilepsy management and thorough medicolegal evaluation to determine the cause of death.